Realidade virtual e experiência do espaço: imersão, fenomenologia, tecnologia - Meneguette, Lucas Correia (2010)
This dissertation aims at researching concepts that emerged from virtual reality studies, through a non-dualistic approach. It starts with a survey about the main technical concepts of virtual reality immersion, presence, and engagement as considered by authors such as Heim, Biocca, Heeter, Grau, Lombard & Ditton. Meanwhile, it is outlined an argument which states that these concepts have emerged from design desires and goals. Afterwards, in order to seek an alternative to the dualism that underlies objectivist approaches of virtual reality, chapters two and three engage to the phenomenological understanding of the lived experience of the space. Therefore, it focuses on studying both Merleau-Ponty's phenomenology of perception and Bachelard's phenomenology of poetic imagination. By clashing this philosophy and those concepts previously considered, two issues have been considered: the body as being-in-the-world and the reverie as poetic activity of inhabiting. These two themes suggest the need to re-articulate the understanding of virtual reality-promoted definitions and applications. On chapter four, in addition to the phenomenological approach, it is discussed the issue of the imagination and participation in game's virtual environment, through the concepts of technical image and imagination from Flusser. Finally, it is suggested a possible way to understand immersion through the phenomenological concept of situation